The quality distribution of jobs and the structure of wages in search equilibrium - Davis, Steven J. (NBER working paper series, 2001)
When match formation is costly and wage determination is decentralized, privately optimal investments in job and worker quality diverge from socially efficient outcomes. To explore this issue, I consider search equilibrium environments with endogenous quality distributions for jobs and workers. I show that a search equilibrium with decentralized wage setting exhibits excessive relative supplies of inferior jobs and inferior workers. Moreover, there are fundamental tensions between the standard wage-setting condition for an efficient total supply of jobs (and workers) in two-sided search models and the conditions required for efficient mixes of jobs and workers. I also derive the efficient wage structure, contrast its properties to the decentralized wage structure and evaluate the welfare and productivity gains of moving to an efficient wage structure. Numerical exercises show that centralized bargaining between a labor union and an employer confederation over the structure of wages can improve productivity and welfare by compressing job-related wage differentials.